STRUCTURE OF MORALE AND PSYCHOLOGICAL CONDITION OF PERSONNEL OF MILITARY UNITS - Сторожук, Н. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article examines the nature and structure of the morale of personnel of military units in terms of performing assigned tasks in the course of special period. Keywords: structure, moral and psychological condition of troops, component personnel, the special period.